Gastrointestinal infantile hemangioma: a rare cause of digestive tract bleeding in children to consider - Cura Esquivel, Idalia; Velásquez Palacios, Carlos Josué; Núñez Ku, Madeline (John Wiley & Sons, 2021)
Intestinal hemangiomas are an infrequent cause of gastrointestinal bleeding and chronic anemia in infants, which diagnosis depends on high suspicion. Propranolol has been described as an effective treatment.